Nilai Budaya Indonesia Dalam Buku Materi Ajar Bahasa Indonesia Untuk Penutur Asing - Harjon Basri; Yuma Rasyid; Fsthiaty Murtadho (Peneliti.net, 2018)
The problem in this research is how is the value of Indonesian culture in the book material of Indonesian language for foreign speakers Level A1, A2, B1, B2, C1, and C2 (BIPA 1, 2, 3, 4, 5 & 6, 7). The method used in this research is descriptive qualitative. From the results of this study obtained information about the value of human life in BIPA 1, 2, 3, 4, 5 & 6, 7. These values ​​can be explained seen in the following explanation. On the Essence of Life from the Self (MH) is divided into (a) life is good, (b) life is bad (c) life is bad but there must be endeavor to live well. The Value of the Essence of Human Work (MK) (a) Work for the living means, (b) Works to supplement the work, (c) Work for position and honor. The Value of Nature of Human Position in Space and Time (MW) (a) Orientation to the past, (b) orientation to the present, (c) Orientation to the future. The Value of Human Relation with Its Surroundings (a) Man is subordinate to nature, (b) Man tries to align himself with nature, (c) Man desires to dominate nature. The Essential Value of Human Relationships with Others (MM). (a) Collateral Orientation, (b) Vertical Orientation, (c) In this study there is no value of individualism values. In this study also found reverse vertical orientation data, namely (1) such as social status because of property / wealth that causes parents to feel afraid of their children. (2) fear of wife, which generally wife respect to husband. (3) the belief in the colonial propaganda, should any propaganda done for bad ends be not trusted or believed to be true